Reminiscence Tours and Pilgrimage Sites - Katja Uusihakala (Suomen Antropologi)
The concept of pilgrimage has recently received fresh attention in the social sciences. One reason for this stems from the fact that migrations, diasporas and similar movements are considered constitutive to the conceptualization and understanding of various contemporary social and cultural processes. The notion of pilgrimage seems to capture both the physical as well as the emotional aspects that such movements contain. This essay examines how members of the ex-Rhodesian diaspora community in South Africa ‘travel back’ to the past in the present in two ways: firstly by concrete heritage journeys to Zimbabwe on reminiscence tours and secondly by constructing memory sites and commemorative venues, where the journeys back to the ‘homeland’ take the form of imaginative travel. It considers how, and if, such constructions and movements related to commemorative practices may be thought of as pilgrimage given that the people themselves perceive, describe and frame such journeys in these terms.